Strategy to build brand image in the footwear industry in Thailand - Watthanaphusit, Komsing; Uthairat, Phitchaya (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The aim of Dissertation: (1) To study the concept of the Strategies to build the Brand Image of the footwear industry in Thailand (2) To study with the process in the Strategies to build the Brand Image of the footwear industry in Thailand 3) To study the indication of the factors that affects the Strategies to build the Brand Image of the footwear industry in Thailand. In this study the researchers had mixed method. Using Quantitative research with Path analysis in model from clients who have used the product brand in the footwear industry in Thailand of 472 samples with depth interview. The questionnaire validated the accuracy of a panel of 5 experts. To calculate the IOC and reliability testing with a correlation with the Cronbach's alpha. The results showed that the Strategies to build the Brand Image of the footwear industry in Thailand Influenced by the positive as well. Customer Loyalty (E = 0.77) elationship management with customers (E = 0.59) Integrated Marketing Communication (E = 0.35) to manage the marketing mix (E = 0.17) and the Trust of customers (.E = 0.08) was statistically significant, respectively. Results of the research showed. Step the Strategies to build the Brand Image of the footwear industry in Thailand must use all elements together, it sort of communication between customers, employees package. This is the direction that needs to be communicated in the same direction. Creating a brand image requires continued innovation. Article history : Accepted 29 January 2016 SIMILARITY INDEX = 0.00